Impact of barbed suture in controlling the dorsal vein complex during laparoscopic radical prostatectomy - Gözen, Ali Serdar; Rassweiler, Jens (Minimally invasive therapy & allied technologies, 2015)
Objective: To compare applications of unidirectional knotless barbed suture and traditional two single polyglactin sutures for dorsal vein complex (DVC) control during laparoscopic radical prostatectomy (LRP). Material and methods: This was a non-randomized, prospective matched-pair pilot study. Thirty-one LRP cases with barbed suture (V-Loc) were match-paired with 31 LRP cases in which traditional two single polyglactin stitches according to patient's prostate volume and body mass index (BMI) were used. Time needed for DVC ligation, DVC control and operation time were recorded. Peri- and postoperative parameters were noted. Statistical analyses were performed. Results: Mean age was 65.4±6.3 years. Mean follow-up was 20.2±3.3 months. Mean BMI and prostate volume were similar in both groups. Mean preoperative clinical stage, Gleason score, and PSA were comparable between both groups. Mean DVC ligature time and mean DVC controlling time in group 1 were statistically shorter than in group 2 (p=0.04, p<0.001). Continence rates were significantly higher in group 1 than in group 2 in early follow-up (p=0.005).
Gesehen am 05.12.2018